Cotyledonoid dissecting leiomyoma of the uterus - Torres-Cepeda, Duly (2022)
Benign smooth muscle tumors are the most common tumors in the female genital tract. Dissecting cotyledonal leiomyoma of the uterus is a rare variant of benign leiomyoma that has unusual growth patterns and shares some features with other variants of dissecting leiomyoma. It has an unusual growth pattern characterized by intramural dissection within the myometrium and with similar appearance of its extrauterine components to placental cotyledons. Its sarcomatoid appearance and unusual character give the impression of malignancy. The diagnosis is made by the characteristic histopathologic findings of the lesion. A case of cotyledonoid dissecting leiomyoma of the uterus is presented.